How do people in prison feel about opt‐out hepatitis C virus testing?. Issue 10 (15th June 2020) - Jack, Kathryn; Linsley, Paul; Thomson, Brian James; Irving, William Lucien
Abstract: The prison population is central to the campaign to eliminate hepatitis C virus as a public health threat. In the UK, this has led to the introduction of a national 'opt‐out' policy, requiring people in prison to be tested for HCV unless they decline, with a target to test 75% of those admitted. However, in a representative prison estate in the East Midlands of England (20, 000 prison entrants per annum) testing rates were only 13.4%. This qualitative study explains why the rates of test uptake are so far short of target. This qualitative study examines the experiences of 45 people in prison about hepatitis C virus testing in an English category C (low security) prison. The data collection method was semi‐structured interviews. The data were coded and analysed according to the research questions, and interpretation of the data was aided by the use of a thematic network approach. The themes Fear, Insufficient Knowledge, Stigma, Privacy, Choice and Prison Life emerged as the principal barriers to test uptake. Test Uptake Facilitators that promoted testing were identified by participants and benefits presented of prison health care being a Health Farm . In order to increase hepatitis C virus test uptake, significant changes and flexibility in the timing, location, and staff deployed to test are required. Providing information to people in prison about hepatitis C virus transmission and treatment may reduce fears and enable the test uptake target to be met and sustained.